COMPARATIVE STUDY ON THE CHANGES OF AROMA COMPONENTS IN THE GRAPE AND DRY RED WINE OF CABERNET SAUVIGNON - B. R. Hu; J. Lu; W. B. Xu; F. M. Zhang (Journal of Animal and Plant Sciences, 2015)
The aroma evolutions in the grape and dry red wine of Cabernet Sauvignon from geographic origin of Ningxia Helan Mountain Eastern Region were studied. The volatile organic compounds were extracted by solvent extraction and analyzed by GC-MS, and their relative contents determined by area normalization. 43 and 56 compounds were separated from the grape and wine respectively, in which 42 from grape and 55 from wine’s volatile organic compounds were identified. Comparing with dry red wine of Cabernet Sauvignon growing different regions in the world, the detection rate was 98.95% and 99.71% of the total peak areas. There were mainly fatty acids, fatty acid esters, lactone, fatty alcohol, alkanols, lower fatty acid, fatty ketones, heterocyclic compounds and other chemical groups. Comparing with dry red wine of Cabernet Sauvignon growing different regions in the world, the higher relative contents and patterns of the volatile organic compounds were similar but characteristic aroma trace components were very different, which lead to a similar and unique aroma and style for the same variety wines. In order to release capability of free aroma substance and improve the quality of dry red wine, the results were significant for wine fermentation technology
Keywords: Cabernet Sauvignon; dry red wine; aroma component; GC-MS